2020
DOI: 10.18632/aging.102640
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α7 nAChR by PNU-282987 improves synaptic and cognitive functions through restoring the expression of synaptic-associated proteins and the CaM-CaMKII-CREB signaling pathway

Abstract: Ligands of nicotinic acetylcholine receptors (nAChRs) are widely considered as potential therapeutic agents. The present study used primary hippocampus cells and APPswe/PSEN1dE9 double-transgenic mice models to study the possible therapeutic effect and underlying mechanism of the specific activation of α7 nAChR by PNU-282987 in the pathogenesis of Alzheimer's disease. The results indicated that activation of α7 nAChR attenuated the Aβinduced cell apoptosis, decreased the deposition of Aβ, increased the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
(65 reference statements)
0
18
0
Order By: Relevance
“…However, the A-582941 treatment did not ameliorate AD-associated changes, such as Aβ deposits, tau phosphorylation, and the presence of inflammatory cells. In contrast, Wang X. L. et al (2020) activated α7 nAChR in primary hippocampal cells and in a APPswe/PSEN1dE9 double-transgenic AD mouse model with PNU-282987. The activation of α7 nAChR improved the cognitive abilities of mice and, among others, reduced the deposition of Aβ in the hippocampus.…”
Section: Therapeutic Applicationsmentioning
confidence: 86%
“…However, the A-582941 treatment did not ameliorate AD-associated changes, such as Aβ deposits, tau phosphorylation, and the presence of inflammatory cells. In contrast, Wang X. L. et al (2020) activated α7 nAChR in primary hippocampal cells and in a APPswe/PSEN1dE9 double-transgenic AD mouse model with PNU-282987. The activation of α7 nAChR improved the cognitive abilities of mice and, among others, reduced the deposition of Aβ in the hippocampus.…”
Section: Therapeutic Applicationsmentioning
confidence: 86%
“…These observations indicated that α7 nAChR may also prevent the loss of synaptic proteins caused by Aβ in vivo . It has been previously reported that the inhibition of the expression levels of α7 nAChR in SH-SY5Y cells by RNA interference increases the toxicity and expression levels of Aβ, which subsequently elevates the expression levels of β-site APP-cleaving enzyme 1 (BACE1) and decreases the expression levels of BACE2 ( 38 , 55 ). In the present study, the expression levels of synaptic proteins were reduced to a greater extent by Aβ in the presence of α7 nAChR silencing, which may be related to the reduced production of Aβ caused by α7 nAChR.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic human Aβ 1-42 was suspended in pre-cooled HFIP at a final concentration of 1 mM; the solution was incubated at room temperature for 60 min and subsequently on ice for 10 min ( 38 ). Aliquots were transferred into non-siliconized microcentrifuge tubes and the HFIP was allowed to evaporate overnight in a hood at room temperature, which was then stored at −80°C ( 38 ). Prior to the treatment of cells, Aβ 1-42 was dissolved in DMSO to obtain a final concentration of 5 mmol/l.…”
Section: Methodsmentioning
confidence: 99%
“…Synaptic plasticity has long been considered as the neurobiological basis of cognition [ 149 ]. Synaptic plasticity also plays an essential role in VaD.…”
Section: Restoration Of Synaptic Plasticitymentioning
confidence: 99%